To find the inverse of the function \( f(x) = \log_{13} x \), we need to express it in a way that allows us to solve for \( x \) in terms of \( y \).
-
Start by rewriting the function with \( y \): \[ y = \log_{13} x \]
-
Now, we convert the logarithmic equation to an exponential one: \[ x = 13^y \]
This means the inverse function can be expressed as: \[ f^{-1}(x) = 13^x \]
From the given options, none of the answers precisely matches \( f^{-1}(x) = 13^x \).
However, the closest equivalent in the options is: \[ f^{-1}(x) = (13)^x \]
So the correct answer is: \[ f^{-1}(x) = (13)^x \]